The low-risk anomaly, cost of capital and IFRS 9 implementation impact: An analysis of South African banks - Nicolson, Duncan (College of Accounting, 2024)
Purpose This dissertation investigates the impact of IFRS 9 implementation on capital ratios and the cost of capital of listed South African banks. In order to investigate this impact, the presence of the low-risk anomaly had to be determined for South African banks. Methodology This dissertation adapts a methodology that has been used to calculate the change in the cost of capital by both Baker & Wurgler (2015) and Fatouh et al. (2020). It is a modified version of CAPM and the weighted cost of capital which includes an error term for the low-risk anomaly. Findings The presence of the low-risk anomaly was discovered in the South African banking equity market. This in combination with a reduction in regulatory capital due to increased credit loss provisions, led to an increase in the cost of capital of South African banks. Practical implications This dissertation helps to add to the growing body of literature around the presence of the low-risk anomaly in South Africa. It also provides an assessment of the impact of the implementation of IFRS 9 on banks that regulators can use to gauge future implementations of regulatory and accounting standards. Investors can also take advantage of the low-risk anomaly and “bet against the beta” to gain additional returns as compared to high-risk portfolios. Value-add New accounting standards are implemented to improve decision-useful information for investors. This dissertation observes the unintended effects of accounting standard implementation on the banking industry in a developing market. The dissertation uses the initial results of IFRS 9 implementation to measure the impact of the accounting standard on banks' regulatory capital and cost of capital.